HealthLine: Speech-based access to health information by low-literate users - Sherwani, J.; Ali, N.; Mirza, S.; Fatma, A.; Memon, Y.; Karim, M.; Tongia, R.; Rosenfeld, R. (2007 International Conference on Information and Communication Technologies and Development, 2007)
Health information access by low-literate community health workers is a pressing need of community health programs across the developing world. We present results from a needs assessment we conducted to understand the health information access practices and needs of various types of health workers in Pakistan. We also present a prototype for speech-based health information access, as well as discuss our experiences from a pilot study involving its use by community health workers in a rural health center.